2020
DOI: 10.1093/eurpub/ckaa166.779
|View full text |Cite
|
Sign up to set email alerts
|

Stress and sleeping disorders among international students of the University of Georgia

Abstract: Background Psycho-physiological factors play a major role in the well-being of students. Available studies have shown that students' sleep habits and stress levels are changing dramatically, especially international students are affected negatively. Increased stress level is associated with decreased cognitive functioning, which negatively affects their academic performance. The main aim of this study was to evaluate sleep disturbance and stress level among international students of the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The students from this study who are smokers had poor sleep quality. Previous studies conducted among UG students have presented the prevalence of stress and sleep deprivation because of poor academic performance [36] which corresponds with the level of psychological problems observed in this study.…”
Section: Discussionsupporting
confidence: 83%
“…The students from this study who are smokers had poor sleep quality. Previous studies conducted among UG students have presented the prevalence of stress and sleep deprivation because of poor academic performance [36] which corresponds with the level of psychological problems observed in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Sleep is a biological regulatory process essential to the nervous system and basic human needs, including metabolism, immunity, and hormonal balance ( 51 , 52 ). Sleep disturbance impacts a considerable number of people ( 53 ), in particular, university students and international students who may experience sleep problems due to academic pressures, environmental changes, and housing conditions, which leads to a deterioration in health and academic performance ( 54 , 55 ). The American Academy of Sleep Medicine recommends regular exercise to maintain healthy sleep ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some studies have shown that students who have low sleep duration at night are likely to have daytime dysfunction [26 -28] which was observed among the participants of this study. There are multivariate factors that can affect the sleep quality of students such as the course of study [29], time management [30,31], academic performance [32,33] and we assumed that the impact of COVID-19 affected the sleep quality of some students. Compared to studies, most foreign students find it difficult to adapt to social life [34,35].…”
Section: Egyptmentioning
confidence: 99%